FUNGSI GAMBAR TIFA PADA DINDING GUA AFOEM DAN GUA YADUMBLU DI KEEROM – PAPUA, KAJIAN ETNOARKEOLOGI - Fairyo, Klementin, Miss (Multikultura, 2026)
This article discusses the function of Tifa drawings on the walls of Afoem cave in Nowai Hamlet and Tifa drawings on the walls of Yadumblu cave in Indangan Hamlet, Yuruf – Amgotro Village, Yaffi District, Keerom Regency - Papua. The Tifa is a traditional musical instrument of the Papuan people; this instrument is an ancestral cultural heritage. The Tifa serves as a cultural artifact and the cultural identity of the Papuan people. The research method is descriptive qualitative, and the topic study uses an ethnoarchaeological approach. The research stages include data collection through literature review, archaeological research reports, books, journals, photo documentation, drawings, and internet data searches. Data processing consists of the analysis of the form and placement of the Tifa drawings on the cave walls and data interpretation. Data interpretation uses an ethnoarchaeological approach, namely conducting an analogical study of Tifa ethnographic data within current community activities. The results of this study indicate that the Tifa drawings on the walls of Afoem cave and the Tifa drawings on the walls of Yadumblu cave function as symbols of the musical instrument accompanying the heru ritual (feast of life and death) and as symbols of male identity.